Fitness and mobility training in patients with Intensive Care Unit-acquired muscle weakness (FITonICU): study protocol for a randomised controlled trial. Issue 1 (December 2016) - Mehrholz, Jan; Thomas, Simone; Burridge, Jane; Schmidt, André; Scheffler, Bettina; Schellin, Ralph; Rückriem, Stefan; Meißner, Daniel; Mehrholz, Katja; Sauter, Wolfgang; Bodechtel, Ulf; Elsner, Bernhard
Abstract Background Critical illness myopathy (CIM) and polyneuropathy (CIP) are a common complication of critical illness. Both cause intensive-care-unit-acquired (ICU-acquired) muscle weakness (ICUAW) which increases morbidity and delays rehabilitation and recovery of activities of daily living such as walking ability. Focused physical rehabilitation of people with ICUAW is, therefore, of great importance at both an individual and a societal level. A recent systematic Cochrane review found no randomised controlled trials (RCT), and thus no supporting evidence, for physical rehabilitation interventions for people with defined CIP and CIM to improve activities of daily living. Therefore, the aim of our study is to compare the effects of an additional physiotherapy programme with systematically augmented levels of mobilisation with additional in-bed cycling (as the parallel group) on walking and other activities of daily living. Methods/design We will conduct a prospective, rater-masked RCT of people with ICUAW with a defined diagnosis of CIM and/or CIP in our post-acute hospital. We will randomly assign patients to one of two parallel groups in a 1:1 ratio and will use a concealed allocation. One intervention group will receive, in addition to standard ICU treatment, physiotherapy with systematically augmented levels of mobilisation (five times per week, over 2 weeks; 20 min each session; with a total of 10 additional sessions). The other intervention group will receive, in addition to standard ICU treatment, in-bed cycle sessions (same number, frequency and treatment time as the intervention group). Standard ICU treatment includes sitting balance exercise, stretching, positioning, and sit-to-stand training, and transfer training to get out of bed, strengthening exercise (in and out of bed), and stepping and assistive standing exercises. Primary efficacy endpoints will be walking ability (defined as a Functional Ambulation Category (FAC) level of ≥3) and the sum score of the Functional Status Score for the Intensive Care Unit (FSS-ICU) (range 0–22 points) assessed by a blinded tester immediately after 2 weeks of additional therapy. Secondary outcomes will include assessment of sit-to-stand recovery, overall limb strength (Medical Research Council, MRC) and grip strength, the Physical Function for the Intensive Care Unit Test-Scored (PFIT-S), the EuroQol 5 Dimensions (EQ-5D) questionnaire and the Reintegration to Normal Living Index (RNL-Index) assessed by a blinded tester. We will measure primary and secondary outcomes with blinded assessors at baseline, immediately after 2 weeks of additional therapy, and at 3 weeks and 6 months and 12 months after the end of the additional therapy intervention. Based on our sample size calculation 108 patients will be recruited from our post-acute ICU in the next 3 to 4 years. Discussion This will be the first RCT comparing the effects of two physical rehabilitation interventions for people with ICUAW due to defined CIP and/or CIM to improve walking and other activities of daily living. The results of this trial will provide robust evidence for physical rehabilitation of people with CIP and/or CIP who often require long-term care. Trial registration We registered the study on 6 April 2016 before enrolling the first patient in the trial at the German Clinical Trials Register (www.germanctr.de ) with the identifierDRKS00010269 . This is the first version of the protocol (FITonICU study protocol).